ANALISIS KEMANDIRIAN DAN EFEKTIVITAS KEUANGAN DAERAH DI KOTA TARAKAN TAHUN 2010-2015 - Ramadhani, Febby Randria (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2016)
This research aimed to investigate the performance of local finance of Tarakan government regarding independency and effectiveness of local finance since 2010-2015 and to investigate the trend of independency and effectiveness of local finance of Tarakan government as far as prospective 2020. Moreover, the instruments for analysis comprised ratio of independency and ratio of effectiveness of local finance and the trend of independency and effectiveness of local finance. Furthermore, this research revealed that: 1) the ratio of independency of local finance of Tararkan since 2010-2015 averaged 159% which was categorized high; 2) Ratio of effectiveness of local finance of Tarakan since 2010-2015 tended to average 92% categorized effective; 3) the trend of independency of local finance exhibited positive trend of which tendency increased started from 2016 to 2020; and 4) the trend of effectiveness of local finance conveyed a positive trend of which tendency increased counted from 2016 to 2020.